Demulsification of oil-rich emulsion and characterization of protein hydrolysates from peanut cream emulsion of aqueous extraction processing. (July 2017) - Li, Pengfei; Zhang, Wenbin; Han, Xin; Liu, Junjun; Liu, Yuanyuan; Gasmalla, Mohammed Abdalbasit A.; Yang, Ruijin
Abstract: In this study, the effect of physical (heating, freezing-thawing), salts (CaCl2 and NaCl) and enzymatic treatments (Protex 6L, Protex 7L, Protex 50FP, Alcalase 2.4L, Papain, phospholipase and Amylase) on free oil recovery yield from peanut cream emulsion of aqueous extraction processing (AEP) were investigated. Proteases were more effective on demulsification than salts and physical methods. The peanut protein hydrolysates were a by-product of AEP. Researches on hydrolysates related to the commercial application of AEP. The degree of hydrolysis and molecular weight (MW) distribution of proteins in cream emulsion were comparable to each other when treating by proteases. Analysis of changes in protein solubility, emulsifying properties, subunit and secondary structure distribution indicated that all the solubility of protein hydrolysates was improved after enzymatic treatment, the emulsifying activity indexes (EAI) of all the hydrolysates were enhanced with the increment in enzymatic time, but only that treated by Protex 50FP significantly higher than control (native proteins in cream emulsion). Moreover, the emulsifying stability indexes (ESI) of all hydrolysates were less than control. Additionally, the results of secondary structure suggested that hydrolysates had decreased the levels of α-helix, β-sheet and β-turn and increased unordered coils level. Highlights: Exploring the quality and application possibility of protein from demulsification. Different demulsification methods on cream emulsion of AEP were explored. Analysis of the characterization of protein hydrolysates from the cream emulsion. Discussing the effect of protein hydrolysis on emulsion stability.